Dynamics of Self-Compassion in Individuals with Childhood Sexual Abuse (CSA) - Rochmawati, Dewi; Winta, Mulya Virgonita I.; Shinta, Margaretha Maria (Yayasan Rumah Ilmu Professor, 2025)
This study aims to understand how the process of self-compassion is formed in individuals who experienced childhood sexual abuse trauma by emphasizing the aspects of subjective experience and the psychological meaning attached. This research method uses a descriptive phenomenological approach involving three adult respondents with a history of such experiences. Data were collected through in-depth interviews and analyzed through the stages of phenomenological reduction, identification of meaning units, transformation of meaning into psychological expressions, and synthesis of essential structures. The results of the study indicate that self-compassion develops gradually through the process of emotional reflection, spiritual awareness, and social support. Three main dimensions of self-compassion, self-kindness, common humanity, and mindfulness were identified in the respondents' recovery process. Self-compassion functions as a trauma recovery mechanism that helps respondents reconstruct their self-narrative from victims to whole and empowered individuals. These findings indicate the urgency of developing self-compassion-based psychological interventions for survivors of childhood trauma.